Respuesta :
Answer:
g(x) = 3x² - 7
Step-by-step explanation:
Transformations of Parent Graph: f(x) = a(bx - h)² + k
a is vertical shrink or stretch
b is horizontal shrink or stretch
(h, k) is the vertex
k is vertical movement
We are given that a = 3, k = -7, so simply plug it into the formula:
g(x) = 3(x - 0)² - 7
g(x) = 3x² - 7
Answer:
g(x) = 3x^2-7
Step-by-step explanation:
f(x) = x^2 is vertically stretched by a factor of 3 and shifted down 7 to form g(x)
we have
g(x) = 3x^2-7
3 = vertical stretch factor
-7 = translation downwards 7 units.